Challenges for the Principal as a Manager Reviewed from the Aspects of His Role and Responsibilities - Yoga Nur Setiawan; Syifa Alfalah; Almaeda Jalaludin; Charles Ilham F; Tamrin Fathoni; M. Neeharika (Tamilis Synex: Multidimensional Collaboration, 2024)
School principals occupy a strategic position in ensuring the effective management and administration of educational institutions. As managers, principals are responsible for planning, organizing, directing, coordinating, and evaluating school resources to achieve educational goals. However, the increasing complexity of educational systems, rapid technological advancement, policy reforms, stakeholder expectations, and organizational demands have created significant managerial challenges for school leaders. This study examines the challenges faced by principals as managers from the perspective of their roles and responsibilities within educational organizations. Using a qualitative literature review approach, the study analyzes contemporary research related to educational management, school leadership, and organizational effectiveness. The findings indicate that principals encounter various challenges, including resource management limitations, human resource development issues, administrative workload, technological adaptation, stakeholder engagement, and resistance to organizational change. Furthermore, balancing managerial duties with instructional leadership responsibilities remains a persistent concern. The study concludes that effective managerial competence, strategic decision-making, communication skills, and adaptive leadership are essential for overcoming these challenges and ensuring sustainable school improvement and educational effectiveness in a rapidly changing environment.